Assessment of the Influence of Cooperative Membership on Farm Business Sustainability and Food Security in Anambra State (West African Journal on Sustainable Development, 2024)
This study investigated the influence of agricultural cooperative membership on farm business sustainability and food security in Anambra State, Nigeria. Agriculture is the backbone of the Nigerian economy because it produces food, creates jobs, supplies industrial raw materials, exports goods for foreign exchange profits, contributes to GDP, and gives farmers a source of income. Agricultural cooperative by default seeks to do same. As such it is pertinent to assess the influence of agricultural cooperative membership on farm business sustainability and food security. A survey was conducted among 221 cooperative members, revealing that the majority were male (67.7%) with some form of tertiary education (55.7%). Most respondents (73.6%) were directly involved in farming. The analysis found a significant positive impact of cooperative membership on both productivity and food security. Compared to non-members, cooperative members experienced a 1.279 unit increase in productivity and a 0.699 unit increase in food security. Based on these findings, the study recommends promoting cooperative membership, particularly among women and individuals with lower education levels.  Additionally, enhanced support for cooperatives, targeted training programs for members, and government initiatives are suggested to further improve productivity and food security. The study also encourages increased investment in research and best practices within agricultural cooperatives.
Keywords: Cooperative Membership; Farm Business; Sustainability; Food Security; Anambra State